2012
DOI: 10.4161/onci.20504
|View full text |Cite
|
Sign up to set email alerts
|

AAV2/IL-12 gene delivery into dendritic cells (DC) enhances CTL stimulation above other IL-12 applications

Abstract: Adoptive transfer of antigen-specific cytotoxic T lymphocytes (CTL) holds significant promise in treating cancer and Th1 response cytokines are critical for their stimulation. Recently we reported that interleukin 7-(IL-7) and interferongamma-(IFNγ) autocrine/T cell gene delivery resulted in superior ex vivo CTL stimulation over paracrine/DC delivery. IL-12 is yet another important Th1 cytokine which affects both DC and T cells. Here, using adeno-associated virus Type 2 (AAV2) gene delivery, IL-12-paracrine/DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Under normal circumstances, endogenous IL‐12 is mainly produced by APCs. Moreover, it has been shown that IL‐12 gene delivery to DCs is superior in stimulating CTLs in an autocrine, paracrine, and even “intracrine” fashion . Therefore, it has been questioned if and how APC‐restricted delivery of IL‐12 in vivo could enhance the stimulation of CTLs , while overcoming toxic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, endogenous IL‐12 is mainly produced by APCs. Moreover, it has been shown that IL‐12 gene delivery to DCs is superior in stimulating CTLs in an autocrine, paracrine, and even “intracrine” fashion . Therefore, it has been questioned if and how APC‐restricted delivery of IL‐12 in vivo could enhance the stimulation of CTLs , while overcoming toxic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have shown successful antitumor activity with reinfusion of unloaded DCs [114] or DCs that are transformed to overexpress various chemokines (such as IL-12 [115117], CCL 21 [118], or IL-23 [119]) or antigen (p53 [120], MART [121], MUC-1 [122], or gp100 [123]). In other instances, DCs loaded ex vivo with TAA [114,115] or pulsed with RNA [124–126] have been reinfused with good effect.…”
Section: Adoptive Immunotherapymentioning
confidence: 99%
“…The rationale behind all these approaches is that DCs become loaded ex vivo with TAAs or TAA-coding molecules, hence becoming able to prime TAA-targeting immune responses upon reinfusion. Additional DC-based anticancer immunotherapies include the targeting of specific TAAs to DCs in vivo [169,[198][199][200][201][202][203][204][205], the use of DC-derived exosomes [206][207][208], and the (re-)administration of autologous or allogeneic DCs amplified, matured and optionally genetically modified ex vivo, but not loaded with TAAs [209][210][211][212][213][214]. In the former setting, TAAs are fused to mAbs, polypeptides or carbohydrates that selectively bind to DCs [169, 198-202, 215, 216], encapsulated in DC-targeting immunoliposomes [217,218], or (3) encoded by DC-specific vectors [219][220][221].…”
Section: Active Immunotherapy Dc-based Immunotherapiesmentioning
confidence: 99%
“…In the former setting, TAAs are fused to mAbs, polypeptides or carbohydrates that selectively bind to DCs [169, 198-202, 215, 216], encapsulated in DC-targeting immunoliposomes [217,218], or (3) encoded by DC-specific vectors [219][220][221]. In the latter scenarios, DCs or their exosomes are administered as a relatively non-specific immunostimulatory intervention [209][210][211][212][213]. Interestingly, one cellular product containing a significant proportion of (partially immature) DCs is currently licensed for use in cancer patients, namely sipuleucel-T (also known as Provenge ® ) (source http:// www.fda.gov).…”
Section: Active Immunotherapy Dc-based Immunotherapiesmentioning
confidence: 99%